Advanced penetration testing for highly-secured environments : the ultimate security guide : learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide - Allen, Lee (Information security specialist) (Community experience distilled., 2012)
Learn to perform professional penetration testing for highly-secured environments with this intensive hands-on guide with this book and ebook.